2012
DOI: 10.1556/oh.2012.29441
|View full text |Cite
|
Sign up to set email alerts
|

The role of intestinal alkaline phosphatase in pediatric inflammatory bowel and celiac diseases

Abstract: Az intestinalis alkalikus foszfatáz enzim alapvető fontosságú a bélnyálkahártya épségének fenntartásában, mivel detoxifi kálni képes a lipopoliszacharidot, amely a Toll-like receptor-4 ligandja. A helytelen immunválasz, valamint a mucosalis barrier sérülése hozzájárulhat a gyulladásos bélbetegség és a coeliakia kialakulásához. Gyulladásos bél-betegségben szenvedő gyermekek gyulladt vastagbél-és újonnan diagnosztizált coeliakiás gyermekek duodenumnyálkahártyájában a csökkent intestinalis alkalikus foszfatáz és … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
2
1
0
Order By: Relevance
“…In addition, significant positive correlations were determined between IAP and I‐FABP, IgE, IL‐4, IL‐13 ( p < 0.01), and eosinophils ( p < 0.05; Table 3 ). Similar to reports by many investigators in intestinal inflammations of various aetiologies (Goldberg et al., 2008 ; Kampanatkosol et al., 2014 ; Kühn et al., 2020 ; Molnar et al., 2012 ; Ok et al., 2020 ; I. B. Yildiz & Ok, 2022 ; R. Yildiz et al., 2018 ), our serum IAP levels were significantly increased in dogs with atopic dermatitis.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, significant positive correlations were determined between IAP and I‐FABP, IgE, IL‐4, IL‐13 ( p < 0.01), and eosinophils ( p < 0.05; Table 3 ). Similar to reports by many investigators in intestinal inflammations of various aetiologies (Goldberg et al., 2008 ; Kampanatkosol et al., 2014 ; Kühn et al., 2020 ; Molnar et al., 2012 ; Ok et al., 2020 ; I. B. Yildiz & Ok, 2022 ; R. Yildiz et al., 2018 ), our serum IAP levels were significantly increased in dogs with atopic dermatitis.…”
Section: Discussionsupporting
confidence: 90%
“…Obesity is one of the chronic inflammatory conditions that have been linked to altered intestinal ALP expression (10). The results of our study showed decreased intestinal ALP activity in the overfed group.…”
Section: Discussionsupporting
confidence: 54%
“…Intestinal ALP is essential in the activation of bacterial Lipopolysaccharides (LPS) through dephosphorylation of its lipid A moiety, resulting in a non-toxic monophosphoryl section. This dephosphorylated monophosphoryl lipid A is not capable of forming a complex with the host's toll like receptor 4 (TLR4) (10).…”
Section: Gunduz Et Al Intestinal Effects Of Gingipainmentioning
confidence: 99%
“…The activity of IAP was the highest at pH 9.7 [23]. IAP is generally secreted in the duodenum, followed by less expression in the jejunum, ileum, and colon [24][25][26]. IAP is largely absent in the stomach in an acidic environment [26,27].…”
Section: Factors Affecting Alp Activitymentioning
confidence: 99%
“…The increased expression of TLR4 may be related to the content of IAP in intestinal mucosa. IAP activity below normal level may lead to IAP/TLR4 imbalance, resulting in increased sensitivity of mucosa to LPS [25]. After treatment, the recovery of intestinal mucosa is very important for the prognosis of the disease.…”
Section: Infant Intestinal Healthmentioning
confidence: 99%